An Unconcealed Reservoir: Case Report of Erosion of Inflatable Penile Implant Reservoir through the Anus - Mark Arthur; Jonathan Canete; Charles Welliver (Case Reports in Urology)
Inflatable penile prosthesis (IPP) involves placement of the fluid reservoir into an abdominal or pelvic location. While the space of Retzius (SOR) was the preferred site for many years, the change from open to robotic prostatectomy made this space less desirable due to the violation of the peritoneum with the robotic approach. Other factors like previous abdominal or pelvic surgeries (particularly inguinal hernia repair with mesh) may also require a change in location of the reservoir during IPP placement. In this report, we discuss a previously undescribed result of alternative reservoir placement (ARP) with erosion of the reservoir through the colon and out of the anus in a man with multiple previous abdominal surgeries. Management of this clinical problem is also discussed.